2017
DOI: 10.1134/s1063784217050073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bias voltage and nitrogen pressure on the structure and properties of vacuum-arc (Mo + Ti6%Si)N coatings

Abstract: Abstract-Effect of deposition conditions in reactive nitrogen atmosphere on the growth morphology, phase composition, structure, and mechanical characteristics (microhardness) of vacuum-arc multilayer coatings obtained using evaporation of the (Ti6%Si) and Mo cathodes is studied with the aid of raster electron microscopy, energy-dispersive elemental microanalysis, and microindentation. It is demonstrated that nitrogen atoms are redistributed to the region of the strongest nitride-forming element (Ti) in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The substrate material was made of a WC-8%Co hard alloy, selected to study physical, mechanical and tribological properties, elemental and phase analysis, and AISI 304 nonmagnetic stainless steel [(up to 0.08)C; (17,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)Cr; (up to 2)Mn; (8)(9)(10)(11)Ni; (up to 0.045)P; (up to 0.03)S; (up to 1)Cu; (up to 0.8)Si; the rest Fe, wt.%] for transmission electron microscopy (TEM) analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The substrate material was made of a WC-8%Co hard alloy, selected to study physical, mechanical and tribological properties, elemental and phase analysis, and AISI 304 nonmagnetic stainless steel [(up to 0.08)C; (17,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)Cr; (up to 2)Mn; (8)(9)(10)(11)Ni; (up to 0.045)P; (up to 0.03)S; (up to 1)Cu; (up to 0.8)Si; the rest Fe, wt.%] for transmission electron microscopy (TEM) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Less often, HEA-based nitride coatings were two-phase coatings. Thus, it was shown that AlCrTiZrNbY HEA coatings produced by vacuum-arc deposition consisted of two nanocrystalline phases [9]. One phase had a bcc lattice with an average crystallite size of 15 nm and a lattice period of 0.342 nm, and the other had an fcc lattice with an average crystallite size of 7 nm and a lattice period of 0.437 nm.…”
Section: Introductionmentioning
confidence: 99%